Associations of lifestyle behaviors with mental health in a nationwide cross-sectional survey of 152,860 Brazilian students - Eduardo Rossato de Victo; Gerson Ferrari; Clemens Drenowatz; Dirceu Solé (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: To evaluate the association between modifiable lifestyle behaviors and mental health indicators in Brazilian adolescents. Methods: This cross-sectional study used data from the 2019 National Survey of School Health including 152,860 students. The lifestyle behaviors and mental health indicators were obtained from a self-reported questionnaire. Logistic regression analyses were used to examine the association between lifestyle behaviors and mental health indicators. Results: Infrequent healthy eating (OR 1.22; 95%CI 1.14-1.31), being inactive (OR 1.82; 95%CI 1.65-2.01), smoking (OR 1.24; 95%CI 1.10-1.40), and irregular school attendance (OR 1.31; 95%CI 1.22-1.40) were associated with not having close friends. Additionally, not having close friends was also associated with unhealthy eating (OR 0.86; 95%CI 0.81-0.92) and alcohol consumption (OR 0.81; 95%CI 0.75-0.87). Infrequent healthy eating (OR 1.29; 95%CI 1.24-1.33), frequent unhealthy eating (OR 1.39; 95%CI 1.35-1.43), being inactive (OR 1.12; 95%CI 1.07-1.18), excessive screen time and sitting (OR 1.10; 95%CI 1.07-1.14 and OR 1.68; 95%CI 1.63-1.73, respectively), smoking (OR 1.26; 95%CI 1.19-1.34), alcohol (OR 1.33; 95%CI 1.28-1.37), drugs (OR 1.13; 95%CI 1.05-1.22), and irregular school attendance (OR 1.53; 95%CI 1.48-1.59) were associated with worse self-rated mental health. Conclusions: Various lifestyle behaviors are associated with different indicators of mental health.